(untitled) - Winckler, Suzanne (New York, 1998)
The Smithsonian Guides to Historic America have undergone their first major revision since their original release. The twelve volumes make up a comprehensive presentation of sites of historical interest & museums covering all States of the Union. In this comprehensive and illustrated guide to the historic places of America, there are descriptions of historic towns, cities, buildings and natural wonders. Also included are details of how common people lived, how fortunes were made, significant characters and America's art and literature. The books in the series are organized for easy reference, with entries arranged geographically and maps provided. Suzanne Winckler is a contributing editor for "Texas Monthly", and writes for several other magazines and newspapers.
Keywords: Historic sites,Địa điểm quan trọng trong lịch sử; Guidebooks,Sách hướng dẫn; Lake States,Bang Hồ Lớn